A Spenser handbook - Jones, H. S. V. (F.S. Crofts & Co., 1930)
"Response to Reform: Composition and the Professionalization of Teaching critiques the politics of labor and gender biases inherent in the composition workplace that prevent literacy teachers from attaining professional status and respect. Scrutinizing the relationship between scholarship and teaching, Margaret J. Marshall calls for a reconceptualization of what it means to prepare for and enter the field of composition instruction."--Jacket.